Popotovanje harmonije? Odnos kitajske države do izseljencev - Bofulin, Martina (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2010)
China has, throughout history, taken advantage of various strategies with the aim of incorporating emigrants into the nation-building projects of the state. A historical review of policies directed to overseas Chinese populations shows an ambivalent disposition toward emigration, ranging from total rejection to glorification. After the introduction of economic and social reforms in 1978, the number of emigrants as well as the number of countries where they settled began to grow. As a consequence, in the last two decades we can observe the formation of Chinese communities in post-socialist countries of Eastern and Central Europe, including Slovenia. This article, using a historical perspective and an analysis of two recent developments, aims to show that the political élites of the Peoplećs Republic of China see the overseas Chinese as crucial for the modernization of the state. The goal of the state is not merely to attract a considerable financial back flow, but increasingly to try to lure overseas Chinese professionals with know-how to return to work in China. The second goal, no less important, is the incorporation of overseas constituencies in the project of international status-building and the dissemination of pro-China views.
Keywords: emigracija; izseljenci; migracijska politika; Kitajska